Molecular survey of Coxiella burnetii in veterinary sample and ticks in Malaysia / Meeta Devi Nurkunasegran - Meeta Devi , Nurkunasegran (2017)
Coxiella burnetii, the causative agent of Q fever, is an intracellular bacterium of medical and veterinary importance. The reservoirs of C. burnetii are extensive which include mammals and arthropods, particularly ticks. The incidence of Q fever in Malaysian population is rarely reported due to the lack of diagnostic facilities. As the organism is difficult to culture, the objective of this study is to use molecular methods, i.e., polymerase chain reaction (PCR) and sequence analysis to determine whether C. burnetii is present in the veterinary samples (milk, vaginal swab and blood samples of domestic livestock) and ticks collected from wildlife, livestock and those from the vegetation. Screening for C. burnetii DNA was conducted using two conventional PCR methods, targeting the transposon like gene IS1111 (Trans-PCR) and the com1 gene (OMP-PCR). The PCR findings were confirmed based on sequence analysis of the amplified fragments or by using a real-time PCR assay. In this study, a total of 173 ticks were examined for the presence of C. burnetii DNA. Ten tick samples (5.8%) were tested positive using Trans-PCR assays and five tick samples (2.9%) were tested positive using OMP-PCR assays. Positive amplification results were obtained from Amblyomma spp., Dermacentor spp., Rhipicephalus spp. and Haemaphysalis spp. ticks. Of 59 milk samples collected from cattle, 17 samples (28.8%) were tested positive by Trans-PCR assays, but none by the OMP-PCR assays. Of 180 vaginal swabs collected from cattle, sheep and goats, 22 samples (12.2%) were positive by Trans-PCR assays and 12 (6.7%) were positive by OMP-PCR assays. Of 103 blood samples collected from cattle, five samples (4.9%) were tested positive by Trans-PCR assays, but none by the OMP-PCR assays. Of the animal samples, the highest percentage of C. burnetii DNA-positive samples from domestic livestock was derived from milk and vaginal samples whereas the lowest percentage was detected in blood samples. The assay targeting the transposon-like gene IS1111 was more sensitive in detecting C. burnetii DNA. Sequence determination of the amplified products confirmed the PCR findings. In view of the detection of C. burnetii DNA in the veterinary and tick samples, awareness for prevention and control of the possible transmission of C. burnetii infection to the local population is necessary.